Implementasi Materi Fiqih Jual Beli Dalam Pembelajaran E-Commerce Di Madrasah Aliyah Persatuan Guru Agama Islam Padang - Ediwan, Ediwan; Khadijah, Khadijah; Sari, Widya (JURNAL ILMIAH EDUNOMIKA, 2025)
This study examines the implementation of Islamic jurisprudence (fiqh) on commercial transactions (buying and selling) within e-commerce learning at Madrasah Aliyah Persatuan Guru Agama Islam Padang through a literature review approach. The research addresses the growing need for integrating fiqh concepts with digital economic practices as online trading becomes increasingly central in students’ daily lives. This study aims to analyze how the principles of fiqh al-buyu’, including pillars, conditions, lawful and unlawful practices, and the prohibition of gharar, can be effectively incorporated into e-commerce learning materials. Using a systematic literature review, relevant books, scholarly articles, and contemporary studies on Islamic commercial law and digital transactions were examined. The findings indicate that e-commerce practices can be aligned with Islamic legal principles when clarity of contract, consent of parties, halal goods, and transparent procedures are ensured, as supported by the Qur’anic principle “wa ahallallāhu al-bay’” (Q.S. Al-Baqarah: 275). The study concludes that integrating fiqh of buying and selling into e-commerce learning enhances students’ understanding of sharia-compliant digital transactions and strengthens their literacy in Islamic economics in the digital era. Keywords: Fiqh of Buying and Selling, E-Commerce, Learning, Islamic Economic Literacy, Digital Transactions